2016
DOI: 10.1176/appi.ps.201500130
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Behavioral Sensing for Outpatients and Inpatients With Schizophrenia

Abstract: Objective The purpose of this study was to examine the feasibility, acceptability, and utility of behavioral sensing in individuals with schizophrenia. Methods Outpatients (N=9) and inpatients (N=11) carried smartphones for two or one week periods, respectively. Device-embedded sensors (i.e., accelerometers, microphone, GPS, WiFi, Bluetooth) collected behavioral and contextual data, as they went about their day. Participants completed usability/acceptability measures rating this approach. Results Sensing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 15 publications
0
106
0
Order By: Relevance
“…Data collection software combined pretimed and behaviorally triggered sensor activation (8,10,11). The microphone was activated every two minutes to capture sound.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection software combined pretimed and behaviorally triggered sensor activation (8,10,11). The microphone was activated every two minutes to capture sound.…”
Section: Methodsmentioning
confidence: 99%
“…For example, working closely with community partners and carefully considering the perspectives of the target population emerged as essential steps towards facilitating the implementation and uptake of a novel mHealth activity tracking system within a low-income African American neighborhood (Yingling et al, 2016). For people with serious mental illness, a recent pilot study showed that a sample of inpatients and outpatients were satisfied and felt comfortable using smartphone sensors for characterizing their daily activity patterns over a 1 to 2 week period (Ben-Zeev et al, 2015). In our prior work, we also observed that popular mHealth technologies appeared feasible for tracking physical activity among a community sample of people with serious mental illness (Aschbrenner, Naslund, Barre, et al, 2015; Naslund, Aschbrenner, Barre, & Bartels, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ben-Zeev and colleagues [17] investigated passive mHealth monitoring through sensors in an smartphone app in a sample of 11 inpatients and nine outpatients with schizophrenia for one or two week periods respectively. They observed that approximately 20% of the sample felt upset by monitoring.…”
Section: Discussionmentioning
confidence: 99%